Review of Climbing Mount Laurel: The Struggle for Affordable Housing and Social Mobility in an American Suburb by Douglas S. Massey et al. - Ioannides, Yannis M. (Journal of Economic Literature, 2017)
Climbing Mount Laurel, authored by a group of sociologists led by Douglas S. Massey, is about the efforts by Mount Laurel Township, NJ, residents to have affordable housing built in their community. From when it was first proposed in 1969 and until the first units were completed in 2000, the project faced extraordinary political opposition, caused a number of landmark court decisions, and motivated affordable-housing legislation by other US states. This review evaluates, from an economics perspective, the lessons learned, as argued by Massey et al., about the impact of affordable housing within the host community and on surrounding communities. (JEL J15, R21, R23, R31, R38, Z13)